Queering Kansas City jazz : gender, performance, and the history of a scene - Clifford-Napoleone, Amber R., 1974- (Expanding frontiers., 2018)
The Jazz Age, a phenomenon that shaped American leisure culture in the early twentieth century, coincided with the growth of Kansas City, Missouri, from frontier town to metropolitan city. Though Kansas City's music, culture, and stars are well covered, Queering Kansas City Jazz supplements the grand narrative of jazz history by including queer identities in the city's history while framing the jazz-scene experience in terms of identity and space. Cabarets, gender impressionism clubs, and sites of sex tourism in Kansas City served as world-making spaces for those whose performance of identity transgressed hegemonic notions of gender, sexuality, race, and class. Amber R. Clifford-Napoleone takes an interdisciplinary approach to provide a critical deconstruction of how the jazz scene offered a space for nonnormative gender practice and performance and acted as a site of contested identity and spatial territory.